Quantification of DNase type I ends, DNase type II ends, and modified bases using fluorescently labeled ddUTP, terminal deoxynucleotidyl transferase, and formamidopyrimidine-DNA glycosylase - David S. Baskin; Marsha A. Widmayer; Martyn A. Sharpe (BioTechniques)
Here we describe the substitution of fluorescently labeled ddUTP for dUTP in the TUNEL assay to allow quantification of generated fluorescence signals by epifluorescence microscopy. The capping of DNase type I 3′OH DNA ends using ddTUNEL was further combined with phosphatase treatment for detection of DNase type II 3′PO4 ends in the same sample using a second round of ddTUNEL. Levels of modified DNA bases in tissues and fixed cultured cells could be interrogated in the ddTUNEL assay with the base modification repair enzyme formamidopyrimidine DNA glycosylase. Using rat mammary gland, from days 1 and 7 of involution, we validate the methodology's ability to label apoptotic nuclei and apoptotic inclusion bodies. In addition, we examined the types of DNA damage and modification that occur in human glioblastoma, U87 cells, following exposure to reactive oxygen stressing agents, chemotherapeutic alkylating agents, and a topoisomerase I inhibitor, irinotecan.